The change of drug utilization in China’s public healthcare institutions under the “4 + 7” centralized drug procurement policy: Evidence from a natural experiment in China - Lu, Jiancheng; Long, Hongfei; Shen, Yuan; Wang, Jing; Geng, Xin; Yang, Ying; Mao, Zongfu; Li, Jinghua (Frontiers in Pharmacology, 2022)
Background: In 2018, Chinese government introduced a novel nationwide policy of centralized drug procurement for off-patent drugs, focusing on improving drug utilization patterns of public medical institutions. Objective: To estimate the impacts of the Chinese centralized drug procurement policy (so-called “4+7” policy) on drug utilization in public medical institutions. Methods: A retrospective natural experimental design and difference-in-difference (DID) method were applied using cross-region data extracted from the national procurement database. Eleven “4+7” pilot cities (intervention group) and eleven non-pilot provinces (control group) were matched. “4+7” policy-related drugs (n=116) were selected as study samples, including 25 drugs in the “4+7” procurement list and their alternative drugs (n=91) that have not yet been covered by centralized procurement policy. “4+7” List drugs were then divided into bid-winning and non-winning drugs according to the bidding results and were sorted into generic and original drugs. Defined daily dose (DDD) was used to standardize the quantity of drugs used. Results: In the one-year procurement period, the overall completion rate of agreed procurement volume reached 191.4% in pilot cities. Under policy impact, the consumption increased by 405.31% in bid-winning drugs (β=1.62, p<0.001) and decreased by 62.28% (β=-0.98, p<0.001) in non-winning drugs. The overall use proportion of bid-winning drugs increased from 17.03% to 73.61% with statistical significance (β=1.48, p<0.001), and increments were also detected in all healthcare settings, regions, and ATC (Anatomical Therapeutic and Chemical) categories (all p-values<0.05). Generics and originators were detected with 67.53% increment (β=0.52, p<0.001) and 26.88% drop (β=-0.31, p=0.006) in consume volume. The use proportion of generics increased from 59.23% to 78.44% with significance (β=0.24, p<0.001), as well as in tertiary hospitals (β=0.31), secondary hospitals (β=0.23), and primary healthcare centers (β=0.11) (all p-values<0.001). The use proportion of relatively quality-guaranteed drugs (i.e. bid-winning & original drugs) increased from 56.69% to 93.61% with significance (β=0.61, p<0.001), and similar increments were also detected in all healthcare settings, regions, and ATC categories (all p-values<0.05). Conclusion: Healthcare providers had good compliance with the “4+7” policy in completing contracted procurement volume. Centralized drug procurement policy promoted drug consumption gradually concentrated on bid-winning drugs, generic drugs, and more importantly, quality-guaranteed drugs.